The value of Trimethylalkylammonium Stearate RQ-20 in the rations of fattening pigs on sudangrass pasture. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
A new chemical made from beef tallow, RQ-20, recently has come on the market and has been claimed to be beneficial for young pigs being fed for market. Its benefit arises from its anti-scouring action and it is said to be effective as a growth promoter. The substance is a white powder with a special trimethylalkylammonium stearate as the active ingredient to control scours. Steamed bonemeal is the carrier and supplies minerals in proper ratio. The two are mixed at the rate of 1 part RQ-20 to 4 parts steamed bonemeal.
Keywords: Swine; Trimethylalkylammonium Stearate RQ-20; Ration; Sudangrass